CXCL13 and CCL11 Serum Levels and Lymphoma and Disease Activity in Primary Sjögren's Syndrome. Issue 12 (25th November 2015) - Nocturne, G.; Seror, R.; Fogel, O.; Belkhir, R.; Boudaoud, S.; Saraux, A.; Larroche, C.; Le Guern, V.; Gottenberg, J. E.; Mariette, X.
Abstract : Objective: Non‐Hodgkin's lymphoma (NHL) is a severe complication of primary Sjögren's syndrome (SS). Ectopic germinal centers (GCs) in the salivary glands are predictors of the occurrence of NHL. Given the association between CCL11 and CXCL13 and ectopic GCs, we assessed the link between these chemokines and NHL, as well as the association between these chemokines and disease activity, in patients with primary SS. Methods: Serum levels of CCL11 and CXCL13 were evaluated by multiplex assay in 385 patients included in the Assessment of Systemic Signs and Evolution of Sjögren's Syndrome (ASSESS) cohort. The association between chemokine levels, B cell biomarkers, and patient subsets was assessed using Spearman's test for continuous data and the nonparametric Mann‐Whitney U test for categorical data. Multivariate analyses were performed to identify parameters associated with lymphoma and disease activity. Results: Seventeen patients had a history of lymphoma, and 5 of them had developed NHL during followup. The median serum levels of CCL11 and CXCL13 in the total cohort were 106.48 pg/ml (interquartile range 69.33–149.85) and 108.31 pg/ml (interquartile range 58.88–200.13), respectively. Patients with lymphoma had higher levels of CXCL13 than did patients without lymphoma ( P = 0.006) and a trend toward a higher level of CCL11 ( P = 0.056). Low C4 and high BAFF levels were associated with NHL on multivariate analysis ( P = 0.01 and P = 0.0002, respectively). CCL11 and CXCL13 levels correlated positively with the rheumatoid factor titer, the κ‐to‐λ free light chain ratio, and the β2 ‐microglubulin level. CXCL13 was the only parameter associated with disease activity on multivariate analysis. Conclusion: These findings demonstrate a link between CXCL13 and CCL11 and disease activity and lymphoma. This highlights the continuum between chronic B cell activation, disease activity, and lymphomagenesis in patients with primary SS.